2016
DOI: 10.20515/otd.34665
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients Prefer Male or Female Physicians/Counselors During Family Planning, Pregnancy and Birth Process? A Sample From Turkey

Abstract: The aim of this study is to investigate women's preferences regarding the gender of the team that provides health care in gynecology and obstetrics, and to find out the factors affecting their preferences. The data of this research were collected from 3 hospitals and 14 small health units. and t tests were used for the statistical evaluation of the data. The study participants are 324 females at the age of 15 to 49, who consulted any of the family planning units of the hospitals or health centers for a family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…Women who are house wives when related to private employed were six times more likely prefer female midwife than male midwife and governmental employed as compared to private employed were three times more likely prefer female midwife than male midwife. This result is in line with the studies conducted in Shashemene and Turkey [18,26]. As female care givers show their gender-related roles they think they do not fear each other and they are more preferred for care, which is believed as a special position for women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Women who are house wives when related to private employed were six times more likely prefer female midwife than male midwife and governmental employed as compared to private employed were three times more likely prefer female midwife than male midwife. This result is in line with the studies conducted in Shashemene and Turkey [18,26]. As female care givers show their gender-related roles they think they do not fear each other and they are more preferred for care, which is believed as a special position for women.…”
Section: Discussionsupporting
confidence: 90%
“…Women's who have no formal education were more likely select female midwives. This is similar with the study conducted in Israel and Turkey [5,26]. The preference of pregnant women for female midwife, decrease as the women's educational status increase.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies indicated that maternal respect during childbirth could be influenced by maternal characteristics (age, educational status, occupation, residence) [1,26,27], health care provider's characteristics (type of profession, estimated work hour per day, sex of profession) [25,[28][29][30][31][32] and health facilities characteristics (type of facility) [1,13,14,25]. The government of Ethiopia also adopts SDG and Growth and Transformation Plan (GTP II).…”
Section: Introductionmentioning
confidence: 99%